Isoespintanol improves the post-thaw quality of stallion semen - RESTREPO, G; ROJANO, B (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to assess the effect of the egg yolk powder in place of fresh egg yolk (EY) in the semen diluent on semen morphological attributes (SMAs) and mobility & velocity profiles measured by computer assisted sperm analyser (CASA) in cryopreserved mithun semen. A total of 25 ejaculates were collected through rectal massage method from five healthy mithun bulls (five ejaculates in each bull) and diluted with the standard tris citrate glycerol (TCG) extender and were splited into four equal aliquots: Gr I: control (20% EY); Gr II, III and IV contained 5, 8 and 10% EY powder, respectively. SMAs, CASA parameters were evaluated following freezingthawing of semen. Result revealed significant (p